Mobile nodes for improving security and lifetime efficiency in wireless sensor networks. Issue 1 (23rd July 2019) - Salah, Mohammed Saïd; Abderrahim, Maizate; Mohamed, Ouzzif; Mohamed, Toumi
Abstract : Purpose: This paper aims to provide an acceptable level of security while taking into account limited capabilities of the sensors. This paper proposes a mobile approach to securing data exchanged by structured nodes in a cluster. Design/methodology/approach: The approach is based on mobile nodes with significant calculation and energy resources that allow cryptographic key management and periodic rekeying. However, mobility in wireless sensor networks aims to increase the security and lifetime of the entire network. The technical methods used in this paper are based on cryptography elliptic curves and key management through a balanced binary tree. Findings: To maintain the effectiveness of critical applications based on wireless sensor networks, a good level of nodes security must be ensured, taking into account their limited energy and computing. Collaboration between powerful mobile nodes provides better coverage and a good key management. Owing to the significant capabilities of the mobile nodes, they can be used to secure critical applications at the same time if needed in applications requiring difficult operations. Originality/value: To compare the performance of the proposed approach with other mobile algorithms, the following metrics are focused on: the energy consumed by normal sensors and cluster heads, the number of packets exchanged during key installation, time to generate and distribute cryptographic keys and the memory used by the different sensors to store keys.